The tarnished garden - Colman, Alyssa (Square Fish, 2023)
Maeve O'Donnell is a student at the Manhattan School for Magic, the newest kindling school in New York, but she struggles to feel like she belongs even though her sister, Izzy, is one of the school's founders because Maeve can't control her magic. When her magic goes terribly awry one day, she finds solace in a secret garden and a neighborhood boy named Avi, a Jewish immigrant who is not allowed to use magic or even come down from his apartment. Maeve befriends a litter of talking kittens in the garden but soon learns someone else is searching for the kittens.